Pré-tratamento organossolve da biomassa de eucalipto utilizando glicerina bruta - Lima, Izabela da Silva (2019)
The search for alternative and renewable energies, capable of minimizing environmental impacts and diversifying the energy matrix, has increased significantly in recent years. With this, the lignocellulosic biomass has been gaining prominence as they are renewable and abundant sources in the country. The Brazilian forestry sector, considered a world power, is a segment with a high capacity in the construction of a green economy, and has intensified investments for the total use of forests, including waste generated, seeking to develop innovative bioproducts essential to future demands mainly for energy. This work aimed to perform the organosolv pretreatment of the residual biomass of the eucalyptus harvest using crude glycerin as a byproduct of the biodiesel production in order to promote the delignification of the biomass and to obtain added value products. An experimental design 2(3-0) was performed to verify the influence of the following variables: temperature (180-220°C), reaction time (60-240 min) and crude glycerin concentration (40-80%). The organosolv pretreatment was performed in a batch reactor, and at the end of each process, the delignified biomass (solid fraction) was obtained, and the liquid phase was denominated black liquor. The "in nature" and pretreated biomasses were characterized as to their chemical composition, structure (X-ray diffraction and crystallinity index), morphology (scanning electron microscopy - SEM), besides calculating the final yield and delignification content, in order to evaluate the efficiency of pretreatment. The black liquor was analyzed by High Performance Liquid Chromatography (HPLC), and the extracted lignin present was separated by acid precipitation to be characterized. The increase in temperature and time had a significant influence on the delignification of the biomass, reaching 83%. Pretreatment conditions provided an average 20% increase in the crystallinity indexes (ICr) of the pretreated biomasses, probably by the removal of amorphous materials such as lignin and hemicellulose during pretreatment, and cellulose permanence in the biomass. Visually, it was possible to notice changes in fiber structure in pretreated biomasses at higher temperatures when compared to "in nature" biomass. In the comparison between crude and pure glycerin, delignification and residual cellulose were higher with crude glycerin as solvent, demonstrating its potential. Considering the results obtained, the use of two residues, forest biomass and crude glycerin, can economically make the process feasible, generating value added products, economic interest and being able to be integrated with the biorefinery concept.